Dating psychological violence among adolescents in a metropolitan region of southeastern Brazil: a school-based study - Isaura Barros Alves Pinto; Franciele Marabotti Costa Leite (Frontiers in Public Health, 2026)
Objective To analyze the prevalence of dating psychological violence among adolescents in the Metropolitan Region of the State of Espírito Santo (ES), Brazil, and its association with socioeconomic and behavioral characteristics and violence experiences. Methods A cross-sectional and analytical study was conducted with 1,238 adolescents aged 14–19, enrolled in public and private schools in the Greater Vitória Metropolitan Region (ES), Brazil, who were in a romantic relationship at the time of the research. Sampling was by cluster and stratification. The outcome variable was dating psychological violence (yes/no), and the independent variables included sociodemographic characteristics, risk behaviors, and previous violence experiences. Absolute and relative frequencies were calculated. Bivariate analysis used Pearson’s chi-square test ( χ 2 ) with a 95% confidence interval. Logistic regression was applied to estimate crude and adjusted associations. Variables with p ≤ 0.20 were included in the multivariate model, while those with p ≤ 0.05 remained in the model. Results We observed that 18.6% (95% CI: 16.5–20.8) of the participants reported having suffered dating psychological violence. The prevalence was 21.7% among girls and 13.1% among boys. Furthermore, higher frequencies of the problem were observed among non-heterosexual adolescents, those who had had sexual intercourse at some point in their lives, those who smoked cigarettes, as well as those who had suffered bullying ( p < 0.05). Conclusion The findings show that early romantic relationships can involve abusive behaviors linked to social vulnerability and prior violence, highlighting the need for education on recognizing abuse and fostering healthy, respectful relationships.